2011
DOI: 10.1158/1055-9965.epi-11-0228
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight Exposure–Mediated DNA Damage in Young Adults

Abstract: Background: Previous experimental studies showed that single ultraviolet B (UVB) light irradiation increased levels of 8-hydroxy-2 0 -deoxyguanosine (8-OHdG), a well-established biomarker of carcinogenesis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 29 publications
0
19
1
1
Order By: Relevance
“…(13) The 8-OHdG levels of our study cohort were not higher than those reported in healthy people by Kato et al (36) Also, the …”
Section: Discussioncontrasting
confidence: 40%
“…(13) The 8-OHdG levels of our study cohort were not higher than those reported in healthy people by Kato et al (36) Also, the …”
Section: Discussioncontrasting
confidence: 40%
“…Statistical analyses using the Mann-Whitney U test and Spearman’s rank correlation test were performed following the method previously described [27]. The SPSS (version 18) software package (SPSS Japan Inc.) was used for these statistical analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, some mutation patterns cannot be explained by UV-induced mutational signatures. These patterns may instead be explained by AID-induced DNA damage or oxidative DNA damage via the production of 8-hydroxydeoxyguanosine by UVB irradiation (56). A previous study showed that UVB irradiation promotes skin tumor formation in mice treated with DMBA alone, suggesting that UV light can act as a tumor promoter and synergize with DMBA (57).…”
Section: Tp53 Mutations In Human Cutaneous Scc In the Uv-protected Rementioning
confidence: 99%